2017
DOI: 10.1074/mcp.m116.065771
|View full text |Cite
|
Sign up to set email alerts
|

The Ser/Thr Protein Kinase Protein-Protein Interaction Map of M. tuberculosis*

Abstract: (Mtb) is the causative agent of tuberculosis, the leading cause of death among all infectious diseases. There are 11 eukaryotic-like serine/threonine protein kinases (STPKs) in Mtb, which are thought to play pivotal roles in cell growth, signal transduction and pathogenesis. However, their underlying mechanisms of action remain largely uncharacterized. In this study, using a Mtb proteome microarray, we have globally identified the binding proteins in Mtb for all of the STPKs, and constructed the first STPK pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 58 publications
(70 reference statements)
0
34
0
Order By: Relevance
“…Protein phosphorylation has emerged as a powerful network, which controls the fundamental physiology as well as the pathogenicity of bacteria. Based on proteome microarray data, STPK‐protein interaction map was constructed, which showed 492 binding partners and 1,027 interactions . However, in order to gain a true insight of the multitude of cellular pathways that are regulated by a specific kinase, high throughput phosphoproteomic studies are the need of the hour.…”
Section: Discussionmentioning
confidence: 99%
“…Protein phosphorylation has emerged as a powerful network, which controls the fundamental physiology as well as the pathogenicity of bacteria. Based on proteome microarray data, STPK‐protein interaction map was constructed, which showed 492 binding partners and 1,027 interactions . However, in order to gain a true insight of the multitude of cellular pathways that are regulated by a specific kinase, high throughput phosphoproteomic studies are the need of the hour.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide regulatory network for BQAPs was compiled from the given regulatory networks (Balázsi et al, 2008;Sanz et al, 2011;Minch et al, 2015). Genome-wide protein interaction network involving BQAPs was generated by merging the derived high-confidence protein interactions (Strong et al, 2003;Wang et al, 2010;Hegde et al, 2012;Liu et al, 2012;Szklarczyk et al, 2017;Wu et al, 2017). The gene expression correlations greater than 0.5 for BQAPs were obtained from Hegde et al (2012).…”
Section: Building Molecular Interaction Networkmentioning
confidence: 99%
“…A recent study using a proteome microarray showed that PknG plays a role in regulating cell wall integrity via regulating biosynthesis of peptidoglycan, a key component of mycobacterial cell walls . PknG also reportedly promotes intrinsic resistance to antibiotics , stress response and biofilm formation .…”
Section: Protein Kinases Regulate Mycobacterial Adaptation and Survivmentioning
confidence: 99%